2016
DOI: 10.1039/c6cp03571j
|View full text |Cite
|
Sign up to set email alerts
|

Solvent effects on the thermal isomerization of a rotary molecular motor

Abstract: As molecular machines move to exciting applications in various environments, the study of medium effects becomes increasingly relevant. It is difficult to predict how, for example, the large apolar structure of a light-driven rotary molecular motor is affected by a biological setting or surface proximity, while for future nanotechnology precise fine tuning and full understanding of the isomerization process are of the utmost importance. Previous investigations into solvent effects have mainly focused on the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…A comprehensive study of a secondgeneration molecular motor substituted with n-butyl chains carried out in over 50 solvents and solvent mixtures showed weak correlation between rotation speed and most solvent effects, suggesting that the inuence of solvent effects on the THI is complex and multi-faceted. 42 There was no signicant correlation found between the effect of solvent polarity on the THI, however this may be partially due to the intrinsic apolarity of the motor studied. However, it was shown that the rate of the THI step has a large dependence on solvent viscosity, 42,138 a phenomenon that was also observed in rst-generation motors tted with rod-like aromatic arms up to 32 Å in lengthso-called molecular stirrers.…”
Section: Rotation Speedmentioning
confidence: 92%
See 1 more Smart Citation
“…A comprehensive study of a secondgeneration molecular motor substituted with n-butyl chains carried out in over 50 solvents and solvent mixtures showed weak correlation between rotation speed and most solvent effects, suggesting that the inuence of solvent effects on the THI is complex and multi-faceted. 42 There was no signicant correlation found between the effect of solvent polarity on the THI, however this may be partially due to the intrinsic apolarity of the motor studied. However, it was shown that the rate of the THI step has a large dependence on solvent viscosity, 42,138 a phenomenon that was also observed in rst-generation motors tted with rod-like aromatic arms up to 32 Å in lengthso-called molecular stirrers.…”
Section: Rotation Speedmentioning
confidence: 92%
“…By designing new families of rotary motors, there are now highly accurate and tuneable tools suited to a myriad of applications involving the control and exploitation of nanoscale dynamics. [40][41][42] As the eld has progressed, the fundamental principles behind the effective design of molecular motors have been better understood. However, the development of molecular motors still faces several challenges, particularly when rotary motors are embedded into more complex multifunctional systems, 43,44 which opens up ample opportunity for novel motor designs to take centre stage.…”
Section: Introductionmentioning
confidence: 99%
“…152,153 However, in a systematic study on a second-generation molecular motor, the THI was found to be strongly solvent-dependent. 155 In particular, in alkane solvents, the t 1/2 of the THI increased with increasing chain length. More polar solvents of the same size also gave longer half-lives, as did alcohols with increasing chain lengths.…”
Section: Photoswitches Relying On the Isomerization About Double-bondsmentioning
confidence: 97%
“…More polar solvents of the same size also gave longer half-lives, as did alcohols with increasing chain lengths. 155 A similar molecular motor dissolved in micelles in water showed a shorter half-life than in short alkanes, while the analogous motor functionalized with water-soluble groups gave a 10-times longer half-live of the metastable state when dissolved in buffer. 152 In conclusion, molecular motors can be readily applied in aqueous environment and have been demonstrated to serve as fully water-soluble switches at low concentrations.…”
Section: Photoswitches Relying On the Isomerization About Double-bondsmentioning
confidence: 99%
“…The speed of the rotary motors is also dependent on the solvent (65,66). In a systematic study of motors with pending arms of varying flexibility and length it was established that solvent polarity plays a minor role, but that in particular enhanced solvent viscosity for motor systems with rigid arms decreases THI drastically (67).…”
Section: Motors Based On Overcrowded Alkenesmentioning
confidence: 99%